Penguatan Kompetensi Guru Madrasah Tsanawiyah Berbasis Kecerdasan Genetik sebagai Solusi Pembelajaran dan Bimbingan Efektif - Asriana Kibtiyah; Jasminto Jasminto; Khoirotul Idawati; Anggara Dwinata; Masyhudan Dardiri; Mohammad Arif Setyabudi (Universitas Nurul Jadid, 2025)
This activity aims to revitalise the role of Madrasah Tsanawiyah (MTs) teachers in improving the effectiveness of learning, caregiving, and counselling services through a genetic intelligence approach. The study was conducted at MTs Madrasatul Qur’an Tebuireng Jombang as part of a Community Service Programme (PKM). Observations and interviews identified three main problems: (1) 19 out of 21 teachers experienced difficulties in implementing differentiated learning due to challenges in recognising students’ characteristics; (2) student conflicts in the form of violence or bullying were not handled optimally; and (3) 4 out of 5 counselling teachers had not yet fully understood students’ potential and problems. The intervention was carried out through training in genetic intelligence based on the STIFIn intelligence model and learning strategies tailored to students’ characteristics. This community service programme consisted of (1) Genetic Intelligence Training, and (2) Learning Strategy Training. Experimental quantitative statistical tests through pre-test and post-test results showed a significant improvement in teachers’ understanding, with an average post-test score increase of 15% in genetic intelligence training and 19% in learning strategy training. The training had a positive impact on enhancing teachers’ competences in (a) recognising students’ potential and learning styles, (b) resolving student conflicts, and (c) providing more targeted and effective counselling services. Furthermore, this approach can be disseminated to other similar educational institutions.